Opportunities and challenges for the Badan Pertanahan Nasional (BPN) in handling land cases in the new normal era - Rahmat Ramadhani; Ummi Salamah Lubis (Faculty of Law, University of Muhammadiyah Malang, 2021)
During the Covid-19 pandemic and the new normal era, it became a separate challenge in resolving land cases by the National Land Agency (BPN). This condition is an opportunity as well as a challenge for the Ministry of ATR/BPN in carrying out its duties as an authorized official in its field. This writing uses legal research methods according to normative law. This type of research used in this writing is library research. Based on the results of the research, it is known that the settlement of land cases by the BPN is currently carried out based on Regulation Number 11 of 2016 as an effort to guarantee legal certainty and justice related to control, ownership, and use of land. One of the steps taken was mediation to reach an agreement, a peace agreement based on current events made mediation mandatory for the parties. That the opportunities and challenges for the BPNin resolving land disputes in accordance with the objectives of the new standard will be changed by the BPN. For this reason, it is necessary to conduct an assessment of opportunities and challenges for them. The Ministry of ATR/ BPN in solving and handling land cases in the new normal era like now.